1982
DOI: 10.1152/jappl.1982.53.4.1050
|View full text |Cite
|
Sign up to set email alerts
|

A conscious dog model for study of regional lung function

Abstract: Using a specially designed mask and steady-state administration of the short-lived radioactive gas 81mKr, we measured the distribution of the ventilation-perfusion ratio (VA/Q) in the lungs of normal conscious standing greyhound dogs during tidal breathing. This model allows measurement of regional lung function unaffected by anesthesia and mechanical ventilation. An assessment of the distribution of VA/Q in the lungs of normal greyhound dogs revealed that topographically, ventilation and blood flow are well m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“… 8,9,14 A recent radiographic study found that NPPE produces caudodorsal lung patterns more frequently than the other causes of non‐cardiogenic PE 14 . It is unknown why NPPE has this predilection for the caudodorsal area, but it could be that because dogs have increased pulmonary blood volume and flow in the caudal lung lobes 15 they are more likely to have transvascular fluid filtration associated with NPPE in this region. This increase of pulmonary blood flow (PBF) in the dorsocaudal area against gravity is also seen in other standing quadrupeds like horses 16 .…”
Section: Discussionmentioning
confidence: 99%
“… 8,9,14 A recent radiographic study found that NPPE produces caudodorsal lung patterns more frequently than the other causes of non‐cardiogenic PE 14 . It is unknown why NPPE has this predilection for the caudodorsal area, but it could be that because dogs have increased pulmonary blood volume and flow in the caudal lung lobes 15 they are more likely to have transvascular fluid filtration associated with NPPE in this region. This increase of pulmonary blood flow (PBF) in the dorsocaudal area against gravity is also seen in other standing quadrupeds like horses 16 .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the distribution of lesions was described as primarily caudodorsal in 47% of dogs, with a diffuse pattern only slightly more common. The predilection of NCPE for a caudodorsal distribution is not completely understood but is likely associated with increased pulmonary blood volume and flow in the caudal lung lobes of dogs 13 . Dogs also have relatively more negative pleural pressures in the dorsal lung fields as compared to ventral regions, which may be relevant in cases of upper airway obstruction 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The predilection of NCPE for a caudodorsal distribution is not completely understood but is likely associated with increased pulmonary blood volume and flow in the caudal lung lobes of dogs. 13 Dogs also have relatively more negative pleural pressures in the dorsal lung fields as compared to ventral regions, which may be relevant in cases of upper airway obstruction. 14 Despite the frequency of caudodorsal distribution, diffuse lesions were most common and should not deter a clinician from a diagnosis of NCPE.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,14 A recent radiographic study found that NPPE produces caudodorsal lung patterns more frequently than the other causes of noncardiogenic PE. 14 It is unknown why NPPE has this predilection for the caudodorsal area, but it could be that because dogs have increased pulmonary blood volume and flow in the caudal lung lobes 15 they are more likely to have transvascular fluid filtration associated with NPPE in this region. This increase of pulmonary blood flow (PBF) in the dorsocaudal area against gravity is also seen in other standing quadrupeds like horses.…”
Section: Discussionmentioning
confidence: 99%